Treatment of secondary oligomenorrhea by electroacupuncture after artifiticial abortion. Prediction of treatment results in women with disorders of autonomic homeostasis - Вол. В. Подольський; О. П. Карпенко; В. В. Подольський (Publishing House TRILIST, 2017)
Changes in reproductive health as menstrual function disorders are common after gynecological diseases and surgery. They are accompanied by high resistance to treatment and risk of adverse effects when using hormone therapy. In fertile aged women with violations of autonomic homeostasis that had artificial abortion, menstrual function disorders are often manifestate as oligomenorrhea. The article presents the results of treatment of women using acupuncture. We used existing techniques electric acupuncture stimulation of biologically active points, which is used for the correction of ovarian-menstrual disorders in fertile aged women. Once the secondary amenorrhea is diagnosed women were divided into 2 groups. First group included women who have recovered after treatment with electroacupuncture regular menstrual cyclicity functions implemented within two menstrual cycles consistent physiological parameters - duration of the cycle, duration and volume of menstrual blood loss. Second group included women, that after two courses of electroacupuncture haven`t had a renewal of menstruation, which was evaluated by the value of these three clinical signs. Further treatment of women conducted by the administration of hormonal therapy in the form of oral contraceptives and other drugs. Treatment and examinations was done by the following algorithm: biologically active point - San-jiao-yin (RP6), Tzu-kung (RS49) bilateral and point Kuan-yuan (J4) were stimulated with a frequency of 4-6 Hz and pulse amplitude value 4.6 mA, which changed within 30 minutes. Before beginning treatment and at the end of each session electroacupuncture measured the pain threshold value in absolute terms milliamperes, dosed by stimulating the skin of the finger on left hand with a frequency of 50-100 Hz and increase of amperage. Notification of pain during the first electrode determined threshold of pain, the maximum amperage corresponds to the threshold of pain tolerance. According to the authors, the use of non-hormonal correction (electroacupuncture) is an effective treatment for such disorders. Predicting the results of treatment of secondary amenorrhea in fertile aged women with violations of autonomic homeostasis that had artificial abortion by pain thresholds may be done using methods proposed by the authors.